Haemorrhoids and anal fissures during pregnancy and after childbirth: a prospective cohort study. (9th May 2014) - Poskus, T; Buzinskienė, D; Drasutiene, G; Samalavicius, NE; Barkus, A; Barisauskiene, A; Tutkuviene, J; Sakalauskaite, I; Drasutis, J; Jasulaitis, A; Jakaitiene, A
<x xml:space="preserve">Abstract</x> Objective To identify the incidence and risk factors of haemorrhoids and fissures during pregnancy and after childbirth. Design Prospective observational cohort study. Setting University hospital and outpatient clinics in Lithuania. Population A total of 280 pregnant women followed up until 1 month after delivery. Methods Women were examined four times through pregnancy and after delivery; those that developed peri‐anal diseases were compared with those that did not. Main outcome measures Incidence, time and risk factors of haemorrhoids and fissures. Results In all, 123 (43.9%) women developed peri‐anal disease: 1.6% in the first trimester, 61% during the third trimester, 34.1% after delivery and 3.3% 1 month after delivery; 114 (40.7%) women were diagnosed with haemorrhoids, seven (2.5%) with haemorrhoids and anal fissure and two (0.71%) with anal fissure. Ninety‐nine (80.5%) women had vaginal delivery and 24 (19.5%) women had undergone caesarean section. Multivariate analysis identified personal history of peri‐anal diseases (odds ratio [OR] 11.93; 95% confidence interval [95% CI] 2.18–65.30), constipation (OR 18.98; 95% CI 7.13–50.54), straining during delivery for more than 20 minutes (OR 29.75; 95% CI 4.00–221.23) and birthweight of newborn >3800 g (OR 17.99; 95% CI 3.29–98.49) as significant predictors of haemorrhoids and anal fissures during pregnancy and perinatal period. Conclusions Haemorrhoids and fissures are common during the last trimester of pregnancy and 1 month after delivery, with constipation, personal history of haemorrhoids or fissures, birthweight of newborn >3800 g, straining during delivery for more than 20 minutes being independently associated risk factors.